Predictable uncertainty about terminal operations in the sea - Hess, Svjetlana; Hess, Mirano (Transport, 2010)
This paper considers a problem of planning short term operations in a bulk terminal faced by port management when making tactical decisions. Ship loading and discharging, cargo stocking, the maintenance and service of facility equipment are regular operations of a bulk terminal which is a subsystem of a sea port the conduct of which is subject to difficult‐to‐predict or unforeseen influences. The problem that port management encounters in day to day operations looks into making the best possible plan with the scheduled duration of operations/states and transition instants, considering various internal and external factors influencing terminal performance. A state and transition model is used for deriving effective solutions to obtaining the state order and state transition time of a bulk terminal with an objective of minimizing operational costs. The behaviour of the terminal is tested applying the stochastic and deterministic method.First published online: 24 Jun 2011